2020
DOI: 10.1159/000512329
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Renal Transplant Recipients: Case Series and a Brief Review of Current Evidence

Abstract: By April 26, 2020, infections related to coronavirus disease 2019 (COVID-19) affected people from 210 countries and caused 203,818 reported deaths worldwide. A few studies discussed the outcome of COVID-19 in kidney transplant recipients. This short series demonstrates our experience in managing COVID-19 disease in renal transplant patients in the absence of strong evidence. We report 8 cases of kidney transplant recipients infected with COVID-19 (median age = 48.5 years; range = 21–71 years), including 4 male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 42 publications
3
25
2
Order By: Relevance
“…All our patients had undergone kidney transplantation many years back with mean duration of 8.4 years, and most of them received the kidney from live‐related donors. This contrasted with most of the literature, which states that cadaveric renal transplants and recently transplanted renal recipients were at a higher risk of acquiring COVID‐19 infection 9,10 . We also had a higher number of female patients, which is in contrast to the available literature 9,10 .…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…All our patients had undergone kidney transplantation many years back with mean duration of 8.4 years, and most of them received the kidney from live‐related donors. This contrasted with most of the literature, which states that cadaveric renal transplants and recently transplanted renal recipients were at a higher risk of acquiring COVID‐19 infection 9,10 . We also had a higher number of female patients, which is in contrast to the available literature 9,10 .…”
Section: Discussioncontrasting
confidence: 81%
“…This contrasted with most of the literature, which states that cadaveric renal transplants and recently transplanted renal recipients were at a higher risk of acquiring COVID‐19 infection 9,10 . We also had a higher number of female patients, which is in contrast to the available literature 9,10 . Similarities to literature include having very high inflammatory and sepsis markers, including ferritin, C‐reactive protein, fibrinogen, and D‐dimers.…”
Section: Discussioncontrasting
confidence: 68%
“…The laboratory abnormalities including lymphopenia; elevated acute biochemical markers, that is, C-reactive protein; procalcitonin; interleukin-6; D dimer; and radiological findings of ground glassing; pneumonia; and fibrosis are associated with poor prognosis [ 14 ]. The nonmodifiable clinical spectrum associated with poor outcomes includes obesity, pre-existing respiratory disease, hypertension, male gender, age >60 years, hypertension, diabetes mellitus, tobacco smoking, pre-existing cardiac diseases, and the first year after transplantation [ 3 , 5 , 15 ]. Elhadedy et al reported, in their series, that more than 90% KTRs required hospitalization, and dyspnoea was the chief complaint in 80% needing ICU service [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…At present, the ideal method of adjusting immunosuppressive drugs in COVID-19 patients who have undergone renal transplant remains unclear, and the discontinuation of antiproliferative drugs, such as azathioprine and mycophenolate, is considered in response to severe infections ( 10 ). Calcineurin inhibitors can be expected to suppress inflammation caused by COVID-19, and since there was a report showing that tacrolimus suppressed the replication of a coronavirus in an in vitro experiment conducted before the COVID-19 pandemic, it is believed that the dose should be either maintained or reduced ( 11 ).…”
Section: Discussionmentioning
confidence: 99%